Investigation of the protective effects of crocin on acrylamide induced small and large intestine damage in rats. (19th May 2018) - Gedik, S.; Erdemli, ME; Gul, M; Yigitcan, B; Gozukara Bag, H; Aksungur, Z; Altinoz, E
Abstract: We investigated repair of acrylamide (AA) induced damage in intestines by administration of crocin. We used 40 male Wistar rats in four groups of 10 animals: control, AA, crocin, and AA + crocin groups. We investigated biochemical and histological changes to small and large intestine. AA ingestion decreased glutathione (GSH) levels and total antioxidant status (TAS) in the intestine compared to the control group, while superoxide dismutase (SOD) and catalase (CAT) activities, and total oxidant status (TOS) and malondialdehyde (MDA) levels were increased. Villi were shortened and villus degeneration was observed in ileum of the AA group. Degeneration of surface epithelium and Liberkühn crypts were observed in colon sections. GSH and TAS levels increased after administration of AA together with crocin, while SOD and CAT levels and TOS and MDA levels decreased; significant recovery of histological damage also was observed. We found that crocin exhibits protective effects on AA induced small and large intestine damage by inhibiting oxidative stress.